Characterization and disruption of exonuclease genes from Streptomyces aureofaciens B96 and S. coelicolor A3(2) - Brnáková, Z; Godány, A; Timko, J (Folia microbiologica, 2009)
Streptomyces aureofaciens B96 produces several intra- and extracellular enzymes with deoxyribonuclease activity. According to the sequence of the previously published gene exoSc from S. coelicolor A3(2), the DNA sequence from S. aureofaciens B96 was amplified, cloned and expressed in E. coli. The protein product of exoSa gene, recExoSa, was also an exonuclease with DNAase and 5'-phosphomonoesterase activities at optimum temperature 37 degrees C and pH 8.0. It degraded only linear DNA (chromosomal, double-stranded and single-stranded) and linear plasmid DNA from both ends, with a preference to blunt ends in comparison with overhang ends. The purified enzyme exhibited no RNAase activity. Both exoSc and exoSa genes were interrupted by the apramycin resistance gene; constructed fragments were transformed into particular streptomyces protoplasts. Mutation caused by exoSa disruption in S. aureofaciens chromosome and mutation by interrupted exoSc in S. coelicolor were lethal.
Keywords: Enzyme Stability; substrátová specifita; Streptomyces aureofaciens; Amino Acid Sequence; Gene Silencing; molekulární sekvence - údaje; bakteriální proteiny; Exonucleases; Molecular Sequence Data; Sequence Alignment; sekvence aminokyselin; klonování DNA; Bacterial Proteins; exonukleasy; Substrate Specificity; sekvenční seřazení; Deoxyribonucleases; umlčování genů; Cloning, Molecular; Streptomyces coelicolor; deoxyribonukleasy; Phosphoric Monoester Hydrolases; stabilita enzymů; fosfatasy